Thomas Jefferson [videorecording (DVD)] : a view from the mountain - Doblmeier, Martin; Herrmann, Edward, 1943-2014 (First Run Features, 2004)
Tells the story of one of America's most complex and enduring figures and his personal and public struggle with an issue that would come to define our nation. Also examines the possible relationship between Jefferson and Monticello slave, Sally Hemings.